PENGALAMAN MAHASISWA DALAM MENJALANI TUGAS PERKEMBANGAN DEWASA AWAL: STUDI FENOMENOLOGI PADA MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI - Septi Mulyani, Nata; Ferdiansyah , Muhammad; Niki Kusaini, Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early adulthood is a transitional phase characterized by increasing demands for independence and responsibility in various aspects of life. Some students in early adulthood still demonstrate suboptimal achievement of developmental tasks, as evidenced by difficulties with time management, procrastination, unstable emotional regulation, indecision, and anxiety about the future. This study aims to understand and interpret the experiences of 2024 Guidance and Counseling students at the University of Jambi who exhibit these conditions. The study employs a qualitative approach using Interpretative Phenomenological Analysis (IPA). The research subjects are eight students selected through purposive sampling based on the results of the Developmental Task Inventory (ITP). Data were collected through in-depth interviews, participant observation, and documentation, and their validity was tested using source, technique, and temporal triangulation. The results indicate that students’ achievement of developmental tasks is not yet optimal but cannot be categorized as a developmental problem. All participants are in a dynamic and ongoing phase of development, characterized by identity negotiation, emotional instability, early-stage career exploration, and a tendency to suppress feelings. Nevertheless, all participants demonstrate reflective awareness and a drive to continue developing. It is concluded that the achievement of early adulthood developmental tasks among students is a gradual, individual, and ongoing process.